BAHASA GAUL DI KALANGAN ANAK SEKOLAH DASAR - Firman Santoso; Asmawati Asmawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTSlang is commonly heard in high school or college age children, at least in middle schoolage. But in this article the researchers examined the slang language that exists inelementary school age children. The researcher used the observation method for 2months in class 6 Primary School. He was positioned as a teacher in class 6 PrimarySchool in MI Al-Jam’iyah Karangtejo, Kedu District, Temanggung Regency, as well asordinary days. Class 6 Primary Schools range in Age from 11 to 13 years. This age canrecord 50,000 words. Data is obtained from student conversations everyday, both inlearning activities in class or when students play in the school environment. Thelanguage of everyday conversation is the typical Javanese language Temanggung(Temanggungan language). From the observations made, the researcher gets a numberof words or slang spoken by Class 6 students. Words or languages that appear reallyare the languages commonly pronounced like teenagers in general, and still in asentence with the typical language of Temanggungan. The choice of words andconditions is indeed the meaning meant in the language. If studied and can find out theorigin of the word, it might say a little misunderstanding, such as the use of the word